PENGARUH CONTENT MARKETING, BRAND ENGAGEMENT DAN ELECTRONIC WORD OF MOUTH (EWOM) TERHADAP KEPUTUSAN PEMBELIAN DI APLIKASI INSTAGRAM (STUDI PADA PENGGUNA DI KOTA MATARAM) - L. Multazam Ibrahim; Fatana Suastrini (Nusantara Hasana Journal, 2024)
This study aims to determine whether content marketing, brand engagement, and electronic word of mouth (e-WOM) partially and simultaneously influence purchasing decisions on Instagram. This research uses a quantitative method with data collection through observation and questionnaires. The sample size is 100 respondents from Instagram users in Mataram City, using purposive sampling. Data were processed using SPSS 26 with analysis techniques including validity tests, reliability tests, classical assumption tests, t-tests (partial), f-tests (simultaneous), determination coefficient tests, and multiple linear regression analysis. The results indicate that content marketing partially influences purchasing decisions on Instagram, brand engagement does not partially influence purchasing decisions, and e-WOM partially influences purchasing decisions. Simultaneously, content marketing, brand engagement, and e-WOM together influence purchasing decisions on Instagram with a significance value smaller than the probability of 0.05 (0.000 > 0.05). The R Square value is 0.372, indicating that 37% of the independent variables explain the dependent variable, while the remaining 63% is influenced by other factors outside the research variables. This study provides insights into the roles of content marketing, brand engagement, and e-WOM in shaping purchasing decisions on Instagram.